β-Cryptoxanthin modulates the response to phytosterols in post-menopausal women carrying NPC1L1 L272L and ABCG8 A632 V polymorphisms: an exploratory study - Granado-Lorencio, F; de las Heras, L; Millán, C. San; Garcia-López, F. J; Blanco-Navarro, I; Pérez-Sacristán, B; Domínguez, G (Genes & nutrition, 2014)
Phytosterol (PS) intake may be used for hypercholesterolaemia in some groups although the presence of non-responders is well known. Carotenoids and PS/cholesterol may compete for the same transporters during absorption. As part of a randomized, double-blind, crossover, multiple-dose supplementation study with β-cryptoxanthin (β-Cx) and PS, single and combined, polymorphisms of ABCG8 (A632V) and NCPL1 (L272L) were determined in 19 post-menopausal women. Subjects carrying CC polymorphism for NCP1L1 (L272L) showed a net increase in total cholesterol and LDL after PS intake but, interestingly, displayed a decrease in both lipid fractions after consuming PS plus β-Cx. For the ABCG8 (A632V) gene, CT/TT carriers consuming PS also displayed an increase in total cholesterol and LDL, but this increment was much lower after the intake of PS plus β-Cx. Additionally, in CC carriers for ABCG8 (A632V), a greater decrease in total cholesterol and LDL was found after the intake of PS plus β-Cx compared to that observed after PS alone. Overall, our results suggest that β-Cx improves the response to PS in individuals carrying specific genetic polymorphisms (i.e. non-responders), opening the possibility to modulate the response to PS by food technology. (ClinicalTrials.gov NCT01074723).